Molecular and immunological analyses of confirmed Plasmodium vivax relapse episodes - Maneerattanasak, S; Gosi, P; Krudsood, S; Chimma, P; Tongshoob, J; Mahakunkijcharoen, Y; Sukasem, C; Imwong, M; Snounou, G; Khusmith, S (BioMed Central, 2017)
Background Relapse infections resulting from the activation hypnozoites produced by Plasmodium vivax and Plasmodium ovale represent an important obstacle to the successful control of these species. A single licensed drug, primaquine is available to eliminate these liver dormant forms. To date, investigations of vivax relapse infections have been few in number.